Electrode wire with porous layer for electrospark machining
By introducing coated holes greater than 2 μm into the coating of the electric spark processing electrode lines and covering them through alloys, the problems of breakage and powder fallout during processing are solved, and higher processing speed and lower powder release are achieved. , improves processing efficiency and product quality.
Patent Information
- Application Number
- CN201980040061.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-07-03
- Filing Date
- 2019-06-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-06-28
AI Technical Summary
The existing electric spark processing electrode lines are prone to break under the combined action of heating and mechanical tension, which limits processing speed and accuracy, and the surface layer material tends to fall off in powder form, resulting in machine tools blockage and fracture.
The electrode wires containing metal cores and coatings are used, and the coating is a broken γ-phase copper-zinc alloy. The coating contains coated holes greater than 2 μm. The holes are covered by copper and zinc alloy alloys. The coated holes are generated by diffusion heat treatment and wire drawing process. , improve the coverage of the coating and the mechanical strength of the electrode lines.
It significantly improves the electric spark processing speed and the integrity of the electrode wire, reduces the risk of powder shedding and machine tool blockage, and improves processing efficiency and product quality.
Smart Images

Figure CN112469523B_ABST
Abstract
Description
Field of the Invention
[0001] The present invention relates to an electrode wire for cutting conductive metal or material by electrical discharge machining in an electrical discharge machining machine.
[0002] A well-known method of electrical discharge machining is to remove material from an electrically conductive workpiece by generating sparks in a machining zone between the workpiece and an electrically conductive electrode wire which extends continuously near the workpiece in the length direction of the wire, is fixed by a guide and is gradually displaced in a transverse direction towards the workpiece by a transverse translation of the electrode wire guide or by a translation of the workpiece.
[0003] A generator connected to the electrode wire via electrical contacts remote from the machining zone establishes a suitable potential difference between the electrode wire and the conductive workpiece to be machined. The machining zone between the electrode wire and the workpiece is immersed in a suitable dielectric fluid. The potential difference causes sparks to appear between the electrode wire and the workpiece, which gradually erode the workpiece and the electrode wire. The longitudinal travel of the electrode wire allows to permanently maintain a sufficient wire diameter to prevent it from breaking in the machining zone. The relative displacement of the electrode wire and the workpiece in the transverse direction makes it possible to cut the workpiece or treat its surface as required.
[0004] Particles dislodged from the electrode wire and workpiece by the spark are dispersed in the dielectric fluid and removed there.
[0005] In order to achieve precise machining, especially for angular cuts with small radii, it is necessary to use electrode wires with small diameters (which can withstand high mechanical loads in the event of breakage) to stretch in the machining zone and limit the vibration amplitude.
[0006] Most modern machines for EDM are designed for use with wire, typically 0.25 mm in diameter and with a breaking load of 400-1000 N / mm2.
[0007] Since EDM is a relatively slow process, it is also necessary to maximize the machining speed, especially the roughing speed. In this patent application, the roughing speed is expressed in mm. 2 / min, that is, the rate of increase of the cutting area, or mm / min at a given workpiece height, that is, the speed at which the electrode wire penetrates the workpiece.
[0008] Until now, it has been assumed that this speed depends directly on the spark erosion energy released in the machining zone between the electrode wire and the workpiece, and therefore on the electrical energy that the electrode wire can transfer to the machining zone. However, the erosive discharge in the machining zone and the Joule effect generated by the current flowing through the electrode wire tend to heat the electrode wire and at the same time reduce its mechanical breaking strength.
[0009] Therefore, one of the limitations of electrode wires used for EDM is that they break under the combined effects of heat and mechanical tension. This forces users to limit the processing capabilities of their spark erosion machines, which also limits processing speeds.
[0010] It has been proposed to use an electrode wire for electrospark machining comprising a metal core and a continuous zinc coating, the function of the coating being to limit the heating of the metal core, since the zinc consumes thermal energy when it evaporates. This makes it possible to increase the machining capacity delivered by the electric discharge machining machine and therefore to increase the machining speed relative to bare copper wire. However, the pure zinc layer is consumed very quickly and cannot protect the core of the electrode wire long enough to cut through thick workpieces.
[0011] Document CH 633739A5 describes an electrode wire for electrospark machining and a method for manufacturing the same, the electrode wire having a core that may be copper or an alloy of copper and zinc, and having a coating that is different from an alloy of copper and zinc and covered with a zinc oxide film. The document mentions that the copper-zinc alloy coating has a porous structure produced by the Kirkendall effect (different diffusion rates of copper and zinc), the electrode wire having a rough surface with 1-2 μm pores, and the zinc oxide film follows the surface roughness. The document teaches that this rough surface structure of the electrode wire is more easily wetted by water used as a dielectric fluid for machining, which increases the cooling function of the electrode wire and allows a larger current to pass.
[0012] Document EP 0 930 131 B1 also describes an electrode wire for electrospark machining and a method for making the same, the wire having a core of a first metal comprising copper, an alloy layer formed on the core, and a surface layer on the alloy layer and composed of a second metal having a vaporization temperature lower than the first metal. The document teaches the advantages of obtaining a porous surface layer of the electrode wire, and the holes are open, because this increases the contact area between the electrode wire and the dielectric fluid used for processing, so as to cool the electrode wire better. The document also teaches that the porous layer promotes the removal of waste from processing. This results in an increase in processing speed. According to the method described in the document, the surface of the electrode wire can crack. The electrode wire is obtained by immersing a brass core having a diameter of 0.9 mm in a molten zinc bath, and then drawing the coated wire into a final diameter of 0.1-0.4 mm.
[0013] In document US 5945010, a method is proposed in which zinc-coated α-phase brass is annealed to produce a peripheral layer of γ-phase brass and then the blank thus obtained is drawn to the final diameter. Drawing produces a surface layer of broken γ-phase brass. The fracture is open to the outside, so that the coverage of the core by the peripheral layer of γ-phase brass is up to 58%. The surface of the resulting electrode wire for electrospark machining is irregular, which the document teaches promotes the removal of waste products from machining, but does not increase the machining speed.
[0014] Document US 8067689 B2 teaches the advantages of a fractured sublayer of γ-phase brass immersed in a substantially continuous outer layer of zinc or ε-phase brass. The electrode wire for electrospark machining is made of a brass core with a diameter of 0.9 mm, which contains 60% copper and 40% zinc and is coated with a 10 μm zinc coating. Heat treatment at 170°C in nitrogen for 6 hours transforms the zinc into the γ-phase brass layer by diffusion. The γ-phase brass layer is then covered with a 10 μm zinc surface layer by electrolysis and reduced to a diameter of 0.25 mm by a wire drawing operation. The document teaches that the wire drawing operation fractures the layer of γ-phase brass, while embedding particles of γ-phase brass produced by the fracture into the zinc of the surface layer. The document also mentions that the zinc of the surface layer can then be transformed into the ε-phase brass by low-temperature heat treatment, and the resulting ε phase can be porous. The pores are open because they can be filled with graphite in turn by the wire drawing operation in the presence of a suspension of graphite particles in an aqueous medium. A disadvantage of such electrode wires for electrospark machining is that some material of the surface layer tends to fall off in the form of powder when the electrode wire is used in an electrical discharge machine. This powder may accumulate in the guide, leading to clogging and undesirable breakage of the electrode wire for electrospark machining.
[0015] Document FR 2 881 973 A1 describes an electrode wire according to the preamble of claim 1. Not explicitly described Figure 2 The dimensions of the coated holes are shown, and no method of obtaining coated holes larger than 2 μm is described.
[0016] In the present description and claims, the structure of the electrode wire for electrospark machining is characterized in particular by the phases of the alloy of the coating constituting the metal core. These phases are described in the phase equilibrium diagram of the copper-zinc system. An example of a phase equilibrium diagram is Figure 6 These phases are characterized by their composition or crystal structure.
[0017] In practice, the expression "β-phase brass" refers to an alloy of copper and zinc with about 45%-49% zinc. At room temperature, this β phase is ordered and rather brittle, usually called β'. Above a certain temperature, the structure becomes disordered and is then called β phase. The transition between β and β' phases is inevitable, but has little effect. As a result, for simplicity, brass will be referred to in this specification by the single expression "β-phase brass".
[0018] In the description and claims, the expression "gamma-phase brass" is used to denote an alloy of copper and zinc, wherein zinc is present in a proportion of about 67% by weight.
[0019] In the description and claims, the expression "epsilon-phase brass" is used to denote an alloy of copper and zinc, wherein zinc is present in a proportion of about 83% by weight.
[0020] In the description and claims, the expression "η-phase brass" is used to denote an alloy of copper and zinc, wherein zinc is present in a proportion of 99-100% by weight.
[0021] "Alpha-phase brass" may have a zinc content of less than 40 wt%, such as about 35 wt%, or even about 20 wt%. Summary of the invention
[0022] There is still a need to process as quickly as possible while avoiding shedding of the material in powder form during processing.
[0023] The present invention surprisingly found that in an electrode wire for electrospark machining having a given core structure and a coating of a fracture layer of an alloy having a zinc content of more than 50% by weight, when there are coated holes in the fracture layer below the electrode wire surface, and when the holes are large enough and fully covered so that the coating covers most of the core, the processing speed can be further increased. This discovery runs counter to the teachings of documents CH 633 739 A5, EP 0 930 131 B1 and US 5945010, which instead suggest that in order to increase the cutting speed, an irregular electrode wire surface layer is made, i.e., containing many open holes facing the outside, promoting contact with a dielectric fluid to cool the electrode wire, and promoting hydraulic turbulence in the dielectric fluid, thereby removing waste from the machining.
[0024] In this regard, in order to compare the technical effects obtained with different coatings, the electrode wires for electrospark machining must have the same core structure. In fact, it is known that the structure of the core has an influence on the speed of electrospark machining. For example, for the same structure of coating, an electrode wire for electrospark machining with a brass core containing 80% copper and 20% zinc has a higher machining speed than an electrode wire for electrospark machining with a brass core containing 63% copper and 37% zinc.
[0025] In this specification and the appended claims, a hole means a space containing no solid matter, contained in a larger volume of solid matter. In the plane of the cross section of the electrode wire for electrospark machining, a hole is a surface in the plane containing no solid matter. The size of a hole in the observation plane is considered to be greater than 2 μm when a circle with a diameter of 2 μm can be drawn inside the hole. Therefore, the size of a hole is the diameter of the largest circle that can be drawn inside it.
[0026] Open holes, such as those present in the irregular surface of the electrode wire for electrospark machining described in the prior art documents cited above, are not covered by solid matter. Therefore, a radial straight line starting from the axis of the electrode wire for electrospark machining and passing through the circle clearly leaves the solid matter area of the observed cross section of the figure.
[0027] On the contrary, in the sense of the present invention, the coated hole appears to be limited by the solid matter on the surface of the electrode wire. In this case, any radial straight line starting from the axis of the electrode wire for electrospark machining and passing through the circle defining the hole size leaves the electrode wire only after passing through the solid matter again.
[0028] In order to observe the holes in the observation plane of the electrode wire cross section, the cross section should be prepared, polished and observed with a microscope with a small depth of field. A depth of field of less than 1 μm may be suitable.
[0029] The longitudinal coverage refers to the length of the electrode wire covered by the coating divided by the total length of the observed longitudinal section of the electrode wire when observing the longitudinal section of the electrode wire.
[0030] A longitudinal section of an electrode wire for EDM machining passes through a plane close to the median longitudinal axis of the electrode wire. This can be checked by measuring the apparent width of the electrode wire, which must be equal to the diameter of the electrode wire, for example within 2%.
[0031] For the purpose of describing and evaluating the number of holes, transverse plane sections of the electrode wire used for EDM are considered, i.e., sections approximately perpendicular to the longitudinal axis of the electrode wire used for EDM. The transverse direction of the plane section is checked by comparing the major and minor axes of the ellipse forming the profile of the transverse plane section. The length of the minor axis of the ellipse must be at least 0.9 times the length of the major axis for the section to be considered transverse, i.e., approximately perpendicular to the axis of the electrode wire.
[0032] Therefore, in order to further improve the speed of electrospark machining, the present invention provides an electrode wire for electrospark machining, comprising:
[0033] - a metal core in one or more metal or metal alloy layers,
[0034] - a coating on a metal core, the coating having an alloy different from that of the metal core and containing more than 50% by weight of zinc,
[0035] - the coating consists of fractured gamma phase copper-zinc alloy,
[0036] - the coating contains coated pores larger than 2 μm,
[0037] in:
[0038] Some or all of the pores are covered with one or more alloys of copper and zinc, wherein the alloy of copper and zinc has more than 58% by weight and less than 100% by weight zinc.
[0039] Although these explanations are not certain, it is believed that sufficiently large covered holes reduce the thermal conductivity of the electrode wire in the radial direction between the outer surface of the electrode wire and the core. Therefore, when the surface of the electrode wire is subjected to the action of machining sparks, its surface temperature rises faster when the covered holes are present than when the covered holes are not present. As a result, the metal surface layer covering the holes of the electrode wire evaporates more quickly. During the short spark duration, this produces a high metal vapor pressure in the arc, and this high pressure increases the removal of material from the workpiece surface. Therefore, the efficiency of the arc is optimized due to the rapid evaporation of the material covering the holes, which is accelerated by the insulation provided by the holes themselves relative to the core of the electrode wire.
[0040] At the same time, since the manufacturing process allows the creation of covered holes, the risk of chipping of the surface layer of the electrode wire can be significantly reduced due to moderate wire drawing, which may release material in the form of powder when using the electrode wire for EDM. In addition, it can be seen that the integrity of the electrode wire is better during the initial rethreading step of the EDM machine, because the diffusion heat treatment can maintain the alloy of copper and zinc below the recrystallization temperature of the core to more than 58% zinc by weight.
[0041] Likewise, as a result of this method, it was observed that a high degree of coverage was obtained, thus for an electrode wire having a diameter of about 0.3 mm, the degree of coverage was greater than 85%, for an electrode wire having a diameter of about 0.25 mm, the degree of coverage was greater than 75%, and for an electrode wire having a diameter of about 0.2 mm, the degree of coverage was greater than 65%.
[0042] More advantageously, for an electrode wire having a diameter of about 0.25 mm, the coverage is greater than 85%.
[0043] More advantageously, provision can be made for some or all of the holes to be covered with one or more alloys of copper and zinc containing more than 78% by weight and less than 100% by weight of zinc.
[0044] According to a particular embodiment, provision can be made for some or all of the pores to be covered with a mixture of an alloy of copper and zinc in the ε and η phases.
[0045] In order to further increase the speed of the roughing process, it can advantageously be provided that the core contains a metallic core and an intermediate layer of an alloy of copper and zinc in the beta phase.
[0046] In this case, the core may be copper or a copper alloy.
[0047] According to an advantageous embodiment, the coating of the electrode wire comprises, on average, at least three coated pores larger than 2 μm per complete cross section of the electrode wire.
[0048] Preferably, the coating of the electrode wire comprises on average at least 5 coated pores larger than 2 μm per complete cross section of the electrode wire.
[0049] It may be advantageous to provide that the coating of the electrode wires comprises coated pores larger than 3 μm, or more advantageously, larger than 4 μm.
[0050] A difficulty that had to be addressed in the design of the present invention was to devise a process that would allow coated holes to be produced in sufficient size and in sufficient number.
[0051] In fact, the methods described in the above cited prior art documents lead to the creation of open holes, ie holes on the outer surface of the electrode wire for electrospark machining, significantly reducing the coverage and producing technical effects different from those sought by the present invention.
[0052] Based on the observation that wire drawing of an electrode wire stock having a coating of an alloy of copper and zinc in a γ phase breaks the alloy layer and creates gaps between alloy blocks, the inventors attempted to cover at least part of the gaps, thereby creating covered holes.
[0053] However, simply covering the alloy layer of copper and zinc in the gamma phase with a surface layer of zinc or some other zinc alloy is not sufficient to obtain covered pores with improved properties.
[0054] - If the zinc surface layer, the η phase copper and zinc alloy surface layer or the ε phase copper and zinc alloy surface layer is too thick relative to the thickness of the γ phase copper and zinc alloy layer, the γ phase copper and zinc alloy layer is not broken, there are no holes, and the processing speed is not improved;
[0055] - If the zinc surface layer, the η phase copper and zinc alloy surface layer or the ε phase copper and zinc alloy surface layer is too thin relative to the thickness of the γ phase copper and zinc alloy layer, the pores are open instead of being covered and the processing speed is not increased;
[0056] - If the γ-phase copper and zinc alloy layer is too thin, the zinc, η-phase copper and zinc alloy or ε-phase copper and zinc alloy will completely or almost completely fill the gaps, leaving no holes or small holes, with little or no effect on the processing speed;
[0057] - if the layer of the alloy of copper and zinc in the gamma phase is too thick, the drawn wire is brittle, i.e. it easily breaks when bent, especially during the automatic rethreading step after the break;
[0058] -Electrode wires can generate a lot of powder when used for EDM if they are not drawn correctly on the appropriate alloy layer.
[0059] According to a first possibility, the zinc coating is produced on top of the interstices that have been produced in the fractured gamma phase of the coating. The interstices are thus captured and constitute the sites of coated pores or the initiation of coated pores.
[0060] According to a second possibility, very slight stretching is carried out on the electrode wire coated with a stack of gamma and eta phases (lightly alloyed zinc).
[0061] Therefore, according to another aspect, the present invention proposes an economical method for producing such an electrode wire, comprising the following steps:
[0062] a) Provide brass core,
[0063] b) covering the core with a layer of electrolytic zinc to form a preliminary blank,
[0064] c) drawing the preliminary blank for the first time to a diameter of about 120% of the final diameter,
[0065] d) subjecting the drawn preliminary blank to a diffusion heat treatment at a temperature between about 170° C. and about 180° C. for about 2 h, the thickness of the zinc layer, the temperature and the duration being selected to produce, by diffusion between the zinc of the coating and the brass of the core, a blank having a sublayer of gamma brass, an intermediate layer of epsilon brass and an outer layer of zinc or eta brass,
[0066] e) The billet thus dispersed is subjected to a second cold drawing to obtain the final diameter.
[0067] During the second wire drawing process, the γ phase brass breaks.
[0068] During the second wire drawing process, the ε-phase brass layer and the surface zinc only very partially fill the voids created between the γ-phase blocks, resulting in covered pores.
[0069] By subsequent heat treatment at a low temperature of about 140°C, the outer layer of zinc or η phase brass covering the pores can be transformed into the ε phase or γ phase without core recrystallization, ie without transformation from a work-hardened state to an annealed state.
[0070] Preferably, the first drawing reduces the diameter by about 40%-78%.
[0071] Other methods of obtaining coated holes are disclosed in the description given below.
[0072] Among the methods described, preference is given to those which are particularly suitable for industrial production, since they are easy to implement due to the reduced number of heat treatments carried out on electrode wire diameters which are significantly larger than the final diameter.
[0073] BRIEF DESCRIPTION OF THE DRAWINGS
[0074] Other objects, features and advantages of the present invention will become more apparent from the following description of specific embodiments with reference to the accompanying drawings, in which:
[0075] - Figure 1 is a schematic perspective view of an electrode wire for electric discharge machining according to the present invention;
[0076] - Figure 2 is a first embodiment of the core of the electrode wire, Figure 1 an enlarged schematic cross-sectional view of a middle electrode line;
[0077] - Figure 3 is a second embodiment of the core of the electrode wire, Figure 1 an enlarged schematic cross-sectional view of a middle electrode line;
[0078] - Figure 4 is based on Figure 1 An enlarged schematic partial longitudinal cross-sectional view of a portion of an electrode line;
[0079] - Figure 5 An example of a phase equilibrium diagram for a copper-zinc system is shown;
[0080] - Figure 6 is a partial cross-sectional view of an electrode wire according to the prior art of document US 8067689;
[0081] - Figure 7 is a schematic partial cross-sectional view of an electrode wire sample A according to Example 1 of the present invention;
[0082] - Figure 8 is a schematic partial cross-sectional view of an electrode wire sample B according to Example 2 of the present invention;
[0083] - Fig. 9 is a schematic partial cross-sectional view of an electrode wire sample E according to Example 5 of the present invention;
[0084] - Fig.10 is a schematic partial cross-sectional view of an electrode wire sample F according to Example 6 of the present invention;
[0085] - Fig.11 is an optical microscope photograph of a cross section of an electrode wire sample B of the present invention;
[0086] - Fig.12 yes Fig.11 An optical microscope photograph of the longitudinal section of the electrode wire sample B;
[0087] - Fig.13 is an optical microscope photograph of a cross section of an electrode wire sample G having a diameter of 0.25 mm according to the present invention;
[0088] - Fig.14 yes Fig.13 Optical microscope photograph of the longitudinal section of the middle electrode wire sample G;
[0089] - Fig.15 yes Fig.13 An optical microscope photograph of the surface of the middle electrode wire sample G; and
[0090] - Fig.16 : is an optical microscope photograph of a cross section of an electrode wire sample G having a diameter of 0.30 mm according to the present invention. DETAILED DESCRIPTION
[0091] In the embodiment shown in the figures, an electrode wire 1 for electrospark machining comprises a metal core 2 covered with a coating 3 of thickness E3, the coating 3 comprising fractured gamma-phase brass.
[0092] exist Figure 2 In the embodiment shown, the metal core 2 comprises a single layer of a metal or metal alloy, for example an alloy with 63% copper and 37% zinc, or an alloy with 80% copper and 20% zinc.
[0093] exist Figure 3 In the embodiment shown, the metal core 2 comprises two different metal or metal alloy layers, which differ in that there is a metal core 2a (eg alpha-phase brass) and an intermediate layer 2b of a beta-phase copper and zinc alloy.
[0094] exist Figure 3 In the same embodiment of , the coating 3 comprises an inner layer 3a of an alloy of copper and zinc (ie in the form of blocks) having a fractured γ phase, and an outer layer 3b of zinc or an alloy of zinc and copper in the ε phase with a thickness E4.
[0095] Now let's consider Figure 4 , which schematically shows an enlarged Figure 1 A partial view of a radial region of the coating 3 covering the core 2 in a longitudinal section over a portion of the length L of the electrode wire 1 .
[0096] The coating layer 3 having a fracture structure includes coated pores 5a, 5b, 5c, 5d, and 5e.
[0097] Figure 4 The dimensions of the coated holes are shown. We can see that, for example, in the coated holes 5a and 5b, there is an inner cavity in which a circle 7 can be drawn. When the circle 7 is in contact with the opposite wall of the cavity, the diameter of the circle 7 defines the dimensions of the hole.
[0098] The holes, such as hole 5b, are considered to be "covered" because a radial line, such as line D1, starting from the axis II of the electrode line and passing through the circle 7, leaves the electrode line only after passing through the solid material 6 again. Similarly, when the circle 7 is covered by the solid material 6, the hole is considered to be "covered".
[0099] exist Figure 4In the illustration of , the holes 5c, 5d and 5e are completely covered, in the sense that no radial straight line passes through them to come out of the electrode wire without passing through the solid material again. In other words, observing the outer surface of the electrode wire in the radial direction, the inner cavity constituting the volume of the hole cannot be seen. In contrast, the holes 5a and 5b are covered, but only partially covered, in the sense that a radial straight line passing through them can come out of the hole in the space shown with the lengths L1 and L2 without passing through the solid material again. In other words, observing the outer surface of the electrode wire in the radial direction, the inner cavity constituting the volume of the hole 5a or 5b can be at least partially seen.
[0100] Figure 4 Also shown is the longitudinal coverage Tc of the coating 3 covering the metal core 2. In the longitudinal cross section of the observed electrode wire, the length of the core 2 not covered by the coating 3 is equal to the sum of the lengths L1 and L2 of the space (according to which the radial straight line passing through the holes 5a and 5b can come out of the holes without passing through the solid substance) at the total length L. Then, the coverage Tc is defined by the following formula:
[0101] Tc = [(total length) - (uncovered length)] / (total length) = 1 - (L1 + L2) / L
[0102] Several embodiments of electrode lines of this type comprising covered holes will now be described.
[0103] In all these examples, the wire drawing step was carried out by injecting a 5-10% by volume emulsion of oil in water into the wire drawing die. The heat treatment step was carried out in a free atmosphere without special precautions to avoid the presence of oxides on the outer surface of the electrode wire.
[0104] Example 1
[0105] In this first embodiment, the electrode wire (sample A) was manufactured by the following method:
[0106] - Take a brass core with a diameter of 1.25 mm and containing 63% copper and 37% zinc,
[0107] - depositing on this core a first zinc layer having a thickness of 6 μm,
[0108] - Pulled to 0.46mm,
[0109] - a diffusion heat treatment is carried out to obtain an outer layer of gamma brass of about 4 μm thickness; in practice, the heat treatment can be carried out at 180°C for about 6 hours,
[0110] - Pulled to 0.30 mm: the γ phase breaks into blocks of about 5 μm, leaving gaps between the blocks,
[0111] - depositing a zinc layer about 2 μm thick,
[0112] -Pull to 0.25mm.
[0113] exist Figure 7 Such an electrode wire sample A is schematically shown in a partial cross section in FIG.
[0114] It was found that in this electrode wire A, coating pores 5a were observed in the cross section of the electrode wire. In fact, in the coating 3 covering the core 2, the ductile zinc of the outer layer 3b only partially filled the voids existing between the blocks of the γ-phase brass layer 3a. However, the number of coating pores 5a was small and the size was small (less than about 2 μm).
[0115] Subsequently, heat treatment is performed at low temperature (about 60°C, 48 hours) to produce an electrode wire (sample A′), in which the zinc outer layer 3b covering the hole 5a is transformed into the α-phase brass by diffusion, while the core 2 does not recrystallize and does not cause the covered hole to disappear.
[0116] Example 2
[0117] In this second embodiment, the electrode wire (sample B) was manufactured by the following method:
[0118] - Take a brass core with a diameter of 1.25 mm and containing 63% copper and 37% zinc,
[0119] - depositing on this core a first zinc layer with a thickness of 20 μm,
[0120] - Pull to 0.30mm,
[0121] - a diffusion heat treatment at 180°C for 2 hours to partially transform the zinc outer layer into a 6 μm γ-phase brass layer; the coating then comprises a γ-phase brass layer near the core, and a 5 μm ε-phase brass outer layer,
[0122] -Pull to 0.25mm.
[0123] This electrode wire sample B Figure 8 It is schematically shown in a partial cross section.
[0124] It was found that in this electrode wire B, coating holes 5a, 5b, 5c can be observed in the cross section of the electrode wire. In the coating 3 covering the electrode wire core 2, the γ phase of the layer 3a was broken into pieces during the second wire drawing process. The outer layer 3b of the ε phase only very partially filled the gaps created between the pieces of the γ phase layer 3a, leaving the coating holes 5a, 5b, 5c, which are more numerous and larger (possibly exceeding 4 μm). The longitudinal coverage is greater than 90%.
[0125] By subsequent low temperature heat treatment (at a temperature of about 180°C for 4 hours), the ε phase outer layer 3b covering the holes can be transformed into γ phase brass without recrystallization of the core 2 causing the covering holes 5a, 5b, 5c to disappear.
[0126] exist Figure 8 In FIG. 8 , a crack 8 is schematically shown, which is significantly different from the coated hole of the present invention in terms of shape and volume, and the crack opens on the surface of the electrode line.
[0127] Fig.11 and Fig.12 The photographs in show the presence of coated holes in the longitudinal section and the cross section of the electrode wire B, respectively.
[0128] Example 3
[0129] In this third embodiment, the electrode wire (sample C) was manufactured by the following method:
[0130] - Take a brass core of 1.20mm diameter, containing 80% copper and 20% zinc,
[0131] - depositing on this core a first zinc layer having a thickness of 30 μm,
[0132] - A first heat treatment at 385°C for 20 hours to obtain: a β phase sublayer of about 60 μm thick, an outer γ phase layer of about 15 μm thick,
[0133] -Pulled to 0.62mm; γ phase fracture,
[0134] - Apply a 3μm zinc coating on the fractured gamma phase, which was previously degreased and deoxidized,
[0135] - Pull to 0.25mm,
[0136] - Heat treatment at 130°C for 5 hours.
[0137] The surface zinc is converted into the ε-phase brass.
[0138] It was found that in this electrode line C, the longitudinal coverage obtained was about 90%. Covered holes can be observed in the cross section of the electrode line. Some of these holes may be larger than 3 μm. On average, more than 3 covered holes were observed in the entire cross section of the electrode line.
[0139] Example 4
[0140] In this fourth embodiment, the electrode wire (sample D) was manufactured by the following method:
[0141] - Take a brass core of 1.20mm diameter, containing 80% copper and 20% zinc,
[0142] - depositing on this core a first zinc layer having a thickness of 38 μm,
[0143] - a first heat treatment at 395°C for 22 hours to obtain: a β phase sublayer of about 76 μm thick and a γ phase outer layer of about 15 μm thick,
[0144] -Pulled to 0.62mm; γ phase fracture,
[0145] - A second heat treatment at 327°C for 7 hours; we obtained a 39 μm thick layer of β-phase brass, and an 8 μm layer of the broken γ-phase brass block also containing the β-phase,
[0146] - 6.5 μm zinc coating on the fractured gamma phase, previously degreased and deoxidized,
[0147] - Pulled to 0.42mm,
[0148] - a third heat treatment at 145°C for 32 hours, resulting in a coating comprising an inner layer of β-phase brass 16 μm thick and a layer of γ-phase brass 14 μm thick,
[0149] -Pull to 0.25mm.
[0150] It was found that in this electrode line D, the longitudinal coverage obtained was about 86%. Covered holes can be observed in the cross section of the electrode line. Some of these holes may be larger than 4 μm. On average, more than 5 covered holes larger than 2 μm were observed in the entire cross section of the electrode line.
[0151] Example 5
[0152] In this fifth embodiment, the electrode wire (sample E) was manufactured by the following method:
[0153] - Take a brass wire of 1.25mm diameter, containing 63% copper and 37% zinc,
[0154] - depositing on this core a first zinc layer 14 μm thick,
[0155] - Pull the wire to 0.827mm,
[0156] - The blank thus obtained is subjected to a diffusion heat treatment until the coating surface no longer has zinc; in practice, the heat treatment can be carried out at 180°C for 4 hours. We obtain a layer of gamma brass of about 13 μm and a surface layer of epsilon brass of about 7 μm thick, without any traces of zinc,
[0157] -Pull to 0.25mm.
[0158] This electrode wire sample E Fig. 9 The partial cross section is schematically shown.
[0159] It was found that in this electrode wire E, a longitudinal coverage of about 86% was obtained. The γ-phase brass layer 3a was broken, including brass pieces of varying thickness, up to 12 μm thick. Coated holes 5a, 5b, 5c, 5d can be observed in the cross section of the electrode wire. Some of these holes may be larger than 4 μm. On average, over the entire cross section of the electrode wire, in the coating 3 covering the core 2, more than 5 coated holes larger than 2 μm were observed.
[0160] exist Fig. 9 FIG. 4 schematically shows a crack 8 which is significantly different from the coated hole of the present invention in shape and volume and opens on the surface of the electrode line.
[0161] Example 6
[0162] In this sixth embodiment, the electrode wire (sample F) was manufactured by the following method:
[0163] - Take a brass core with a diameter of 1.25 mm and containing 63% copper and 37% zinc,
[0164] - depositing on this core a first zinc layer with a thickness of 20 μm,
[0165] - Pulled to 0.827mm,
[0166] - a first heat treatment at 180°C for 5 hours to obtain: a sublayer of a copper and zinc alloy in the γ phase of about 15 μm thick, an intermediate layer of a copper and zinc alloy in the ε phase of about 6 μm, an outer layer of a light alloyed copper and zinc alloy in the η phase of about 6 μm thick,
[0167] - Pulled to 0.25 mm; the gamma phase breaks and the coating covering the core is a mixture of copper-zinc alloy chunks in the gamma phase, the pores between the chunks are covered by a mixture of copper-zinc alloy in the epsilon and eta phases.
[0168] exist Fig.10 Such an electrode wire sample F is schematically shown in a partial cross section in FIG.
[0169] It was found that in this electrode line F, the longitudinal coverage obtained was greater than about 90%. Covered holes 5a, 5b, 5c can be observed in the cross section of the electrode line. Some of these holes may be greater than 4μm. On average, more than 5 covered holes greater than 2μm were observed in the entire cross section of the electrode line.
[0170] Subsequently, the electrode wire (sample F') is produced by heat treatment at low temperature (about 60°C, 48 hours), in which the zinc outer layer 3b covering the holes is transformed into the ε phase brass by diffusion, and the core 2 does not recrystallize, which does not cause the covered holes 5a, 5b, 5c to disappear.
[0171] Then, a second heat treatment is carried out at about 180°C for 2 hours to produce an electrode wire (sample F"), in which the outer layer 3b of the ε-phase copper and zinc alloy covering the holes is transformed into the γ-phase copper and zinc alloy by diffusion, and the core 2 is not recrystallized, which will not cause the covered holes 5a, 5b, 5c to disappear.
[0172] Example 7
[0173] In this seventh embodiment, the electrode wire (sample G) was manufactured by the following method:
[0174] - Take a brass wire of 1.20mm diameter, containing 60% copper and 40% zinc,
[0175] - depositing a 13 μm thick zinc layer on the core,
[0176] - The wire is pulled to 0.464 mm and then the zinc layer is 5 μm thick,
[0177] - the blank thus obtained is subjected to a diffusion heat treatment consisting of increasing the temperature from room temperature to a fixed stage of 140° C. for 11 hours over 4 hours, and then decreasing the temperature to room temperature over 5 hours; the coating then comprises an inner layer of gamma brass of about 6 μm and a surface layer of epsilon brass of about 2 μm thick, without zinc;
[0178] - Gradual drawing to the final diameter, for example by using 5 consecutive dies to reduce to a final diameter of 0.30 mm, or using 8 consecutive dies to reduce to a final diameter of 0.25 mm, or using 10 consecutive dies to reduce to a final diameter of 0.20 mm.
[0179] Fig.13 , 14 15 are optical microscope photographs of the sample electrode wire G with a diameter of 0.25 mm, which are cross-sectional, longitudinal cross-sectional and surface views, respectively. Fig.16 : are optical microscope photographs of sample electrode wires with a diameter of 0.30 mm. The following are marked on these photographs: core 2, broken γ-phase copper and zinc alloy inner layer 3a, ε-phase copper and zinc alloy outer layer 3b and coated holes 5a.
[0180] It can be seen that in such an electrode wire G, when the diameter of the electrode wire is 0.30 mm, the longitudinal coverage obtained is about 88%. When the diameter of the electrode wire is 0.25 mm, the longitudinal coverage is about 77%. When the diameter of the electrode wire is 0.20 mm, the longitudinal coverage is about 66%. The γ-phase brass layer is broken, including a brass block with a substantially constant thickness. Covered holes 5a can be observed in the cross section of the electrode wire. Some of these holes are larger than 2 μm. On average, in the coating covering the core, more than 5 covered holes larger than 2 μm are observed over the entire cross section of the electrode wire.
[0181] Sample B of the second embodiment and sample G of the seventh embodiment are obtained by a method particularly suitable for industrial production, because only one heat treatment is required. In the case of sample G, the heat treatment is carried out on an electrode wire diameter significantly larger than the final diameter, which is even more advantageous in industrial production.
[0182] test
[0183] Comparative processing tests were carried out, demonstrating the beneficial effects of the present invention.
[0184] Processing tests were conducted using electrode wires A, A', B, C, D, E, F, F', F", and G (whose manufacture is described above) to compare them with:
[0185] - a bare copper electrode wire with a diameter of 0.25 mm containing 63% copper and 37% zinc (sample LA),
[0186] - an electrode wire (sample T) with a diameter of 0.25 mm, having a core of a copper-zinc alloy containing 63% copper and 37% zinc, a coating covering practically 100% of the core surface and comprising broken blocks of copper and zinc alloy in the γ phase, said blocks being embedded in a matrix of copper and zinc alloy in the ε phase, which matrix fills the gaps between the blocks of the γ phase. This electrode wire is as described in document US Pat. No. 8,067,689 B2 according to an embodiment in the ε phase,
[0187] - an electrode wire (sample SD2) with a diameter of 0.25 mm, having a core of a copper and zinc alloy containing 63% copper and 37% zinc; a coating having a copper and zinc alloy sublayer in the β phase and a fractured copper and zinc alloy outer layer in the γ phase (i.e. having open pores),
[0188] - an electrode wire (sample SE) with a diameter of 0.25 mm, having a core of a copper and zinc alloy containing 80% copper and 20% zinc, a coating having a copper and zinc alloy sublayer in the β phase and an outer layer of a copper and zinc alloy in the fractured γ phase (i.e. having open pores),
[0189] - Electrode wire (sample SA) with a diameter of 0.25 mm, having a core of a copper and zinc alloy containing 63% copper and 37% zinc, a coating of a copper and zinc alloy in a fractured gamma phase, having an alloy block of substantially constant thickness and showing holes in the cross section, i.e. having open pores.
[0190] All machining tests were performed using a GFMS P350 machine on a steel workpiece with a height of 50 mm (with detached nozzles at 4.4 mm at the bottom and 5.0 mm at the top), using AC CUT VS+0.25 mm technology (ACO=0), changing I from 17 to 18, P from 54 to 45 to provide a machining current of approximately 10 A, and changing FW from 17 to 10.
[0191] Regarding the comparative test for evaluating the powder production during machining, a section of electrode wire of about 1000 linear meters, tensioned with a tension of 10N, was passed through the ceramic wire slot of the EDM machine, the powder was collected on the adhesive surface under the wire slot, and the amount of deposited powder was compared. The comparison was basically visual observation, using five threshold amounts, namely undetectable amount, very little amount, medium amount, large amount and very much amount. The amount standard was obtained by SA, SD2 and SE electrode wires, which are mass-produced electrode wires that the applicant has been selling for several years. The SA wire only produces an undetectable amount of powder during EDM. The SD2 and SE electrode wires only produce very little powder during EDM, and are therefore completely satisfactory.
[0192] The results are listed in the table below.
[0193] Electrode wire <![CDATA[Processing speed (mm 2 / min)]]> Amount of powder Surface state Electrode line LA 83.8 medium Electrode cable SD2 99.8 rare Electrode line SE 106.6 rare Electrode line SA 90 Undetectable Excellent (0.16μm) Electrode wire T 96.0 Very large 0.20μm Electrode line A 94.2 medium Electrode line A' 96.0 medium Electrode wire B 100.3 rare Good (0.20μm) Electrode line C 107.1 big Electrode line D 110.1 rare Electrode line E 101.9 medium medium Electrode wire F 97.0 rare medium Electrode line F' 108 medium Electrode wire F" 110 big medium Electrode wire G (0.25mm) 95 Undetectable Excellent (0.15μm)
[0194] The coated holes of electrode lines A and A' are apparently too small to have a beneficial effect on the processing speed relative to electrode line SD2.
[0195] However, a comparison of the processing speeds of electrode wire A and electrode wire A' shows the advantages of the ε phase over pure zinc or η phase.
[0196] When examining electrode wires B and E with coated holes of sufficient size, we found that the roughing speed was improved relative to electrode wires with the same copper CuZn37 core structure and with a coating with open holes or with small coated holes (electrode wires SD2, A, A').
[0197] In particular, electrode wire E produced by depositing the same amount of zinc as wire A' shows the advantage of having coated pores larger than 4 μm in the coating. In contrast to electrode wire E, electrode wire A' has only pores with a diameter smaller than 2 μm.
[0198] Electrode wire B gives low roughness values in the finishing process, in the order of 0.20 μm Ra. It generates almost no powder when passing through the electrode wire slots of the machine tool. Electrode wire B shows that in order to achieve a balance between high machining speeds, low roughness values and minimal powder release, it may be advantageous to produce coated holes larger than 4 μm covered by the ε phase copper and zinc alloy between the broken pieces of the γ phase copper and zinc alloy of regular thickness. Compared with electrode wire SD2 (whose core has the same composition), electrode wire B shows the advantage of the presence of large coated holes.
[0199] When examining electrode wire D, which has coated holes of sufficient size, we found that the roughing speed was improved relative to an electrode wire having the same copper CuZn20 core structure and having an open-pore coating (electrode wire SE).
[0200] Despite the presence of the coating with the fractured γ phase, ε phase, and covered pores, the electrode wire F has a relatively low processing speed. The presence of η phase zinc appears to be responsible for this result.
[0201] Compared with the electrode wire F, the electrode wire F′ shows an advantage of having coated pores larger than 3 μm in the coating layer of the alloy of copper and zinc having an ε phase and no η phase.
[0202] Electrode wire G gives very low roughness values in finishing. Almost undetectable amounts of powder are generated when it passes through the wire grooves of the machine tool. Electrode wire G shows that, in order to reconcile high machining speeds, very low roughness values and almost undetectable powder release, it may be advantageous to produce covered holes larger than 2 μm covered by the ε phase of copper and zinc alloy between the broken pieces of the γ phase of copper and zinc alloy of regular thickness. Compared with electrode wire SA showing the same structure with broken pieces of the γ phase of copper and zinc alloy of regular thickness, electrode wire G shows the advantage of the presence of covered holes in terms of increasing machining speed.
[0203] The invention is not limited to the embodiments that have just been explicitly described, but comprises several variants and generalizations within the scope of the claims presented below.
Claims
1. An electrode wire (1) for electric spark machining, the electrode wire (1) comprising: - a metal core (2) made of one or more metal or metal alloy layers, a coating (3) on the metal core (2) which has a different alloy than the metal core (2) and contains more than 50% zinc, in: - the coating (3) comprises a copper-zinc alloy layer (3a) of a fractured gamma phase, Features include: - the coating (3) comprises coated pores (5a, 5b, 5c, 5d, 5e) larger than 2 μm, - Some or all of the holes (5a, 5b, 5c, 5d, 5e) are covered by an outer layer (3b) made of one or more alloys of copper and zinc having more than 58% by weight and less than 100% by weight of zinc.
2. The electrode wire according to claim 1, It is characterized in that When the diameter of the electrode wire is about 0.30 mm, the coating (3) covers the metal core (2) with a coverage greater than 85%, when the diameter of the electrode wire is about 0.25 mm, the coverage is greater than 75%, and when the diameter of the electrode wire is about 0.20 mm, the coverage is greater than 65%.
3. The electrode wire according to claim 1, It is characterized in that When the diameter of the electrode wire is 0.25 mm, the coating (3) covers the metal core (2) with a coverage greater than 85%.
4. The electrode wire according to claim 2, It is characterized in that When the diameter of the electrode wire is 0.25 mm, the coating (3) covers the metal core (2) with a coverage greater than 85%.
5. The electrode wire according to claim 1, It is characterized in that Some or all of the holes (5a, 5b, 5c, 5d, 5e) are covered by an outer layer (3b) made of one or more alloys of copper and zinc having more than 78% by weight and less than 100% by weight zinc.
6. The electrode wire according to claim 2, It is characterized in that Some or all of the holes (5a, 5b, 5c, 5d, 5e) are covered by an outer layer (3b) made of one or more alloys of copper and zinc having more than 78% by weight and less than 100% by weight zinc.
7. The electrode wire according to claim 3, It is characterized in that Some or all of the holes (5a, 5b, 5c, 5d, 5e) are covered by an outer layer (3b) made of one or more alloys of copper and zinc having more than 78% by weight and less than 100% by weight zinc.
8. The electrode wire according to claim 4, It is characterized in that Some or all of the holes (5a, 5b, 5c, 5d, 5e) are covered by an outer layer (3b) made of one or more alloys of copper and zinc having more than 78% by weight and less than 100% by weight zinc.
9. The electrode wire according to any one of claims 1 to 8, It is characterized in that Some or all of the holes (5a, 5b, 5c, 5d, 5e) are covered by an outer layer (3b) which is a mixture of an alloy of copper and zinc in ε and η phases.
10. The electrode wire according to any one of claims 1 to 8, It is characterized in that The coating (3) contains, on average, at least 3 coated pores (5a, 5b, 5c, 5d, 5e) larger than 2 μm per complete cross section of the electrode wire.
11. The electrode wire according to any one of claims 1 to 8, It is characterized in that The coating (3) contains, on average, at least 5 coated pores (5a, 5b, 5c, 5d, 5e) larger than 2 μm per complete cross section of the electrode wire.
12. The electrode wire according to any one of claims 1 to 8, It is characterized in that The coating (3) comprises coated pores (5a, 5b, 5c, 5d, 5e) larger than 3 μm.
13. The electrode wire according to any one of claims 1 to 8, It is characterized in that The coating (3) comprises coated pores (5a, 5b, 5c, 5d, 5e) larger than 4 μm.
14. The electrode wire according to any one of claims 1 to 8, It is characterized in that The metal core (2) comprises a metal core (2a) and an intermediate layer (2b) of a β-phase copper and zinc alloy.
15. The electrode wire according to claim 14, It is characterized in that The core (2a) is made of copper or a copper alloy.
16. A method for manufacturing an electrode wire according to any one of claims 1 to 15, comprising the following sequence of steps: - Take a brass core with a diameter of 1.25 mm containing 63% copper and 37% zinc, - depositing on this core a first zinc layer with a thickness of 20 μm, - Pull to 0.30mm, - a diffusion heat treatment at 180°C for 2 hours to partially transform the zinc outer layer into the γ-phase brass layer; the coating then comprises a γ-phase brass layer near the core, and an ε-phase brass outer layer, -Pull to 0.25mm.
17. A method for producing an electrode wire according to any one of claims 1 to 15, The following steps are involved: - Take a brass core with a diameter of 1.20 mm containing 80% copper and 20% zinc, - depositing on this core a first zinc layer having a thickness of 30 μm, - The first heat treatment was carried out at 385°C for 20 hours, resulting in: a β phase sublayer of about 60 μm thick, an outer γ phase layer of about 15 μm thick, -Pulled to 0.62mm; γ phase fracture, - 3 μm zinc coating on the fractured gamma phase, previously degreased and deoxidized, - Pull to 0.25mm, - Heat treatment at 130°C for 5 hours.
18. A method for producing an electrode wire according to any one of claims 1 to 15, The following steps are involved: - Take a brass core with a diameter of 1.20 mm containing 80% copper and 20% zinc, - depositing on this core a first zinc layer 38 μm thick, - The first heat treatment was carried out at 395°C for 22 hours, resulting in: a β phase sublayer of about 76 μm thick, an outer γ phase layer of about 15 μm thick, -Pulled to 0.62mm; γ phase fracture, - A second heat treatment was carried out at 327°C for 7 hours; a 39 μm thick β-phase brass layer was obtained, and an 8 μm layer of the broken γ-phase brass block also containing the β-phase, - Apply a 6.5 μm zinc layer on the fractured gamma phase, previously degreased and deoxidized, - Pulled to 0.42mm, - A third heat treatment was carried out at 145°C for 32 hours, and the resulting coating contained a 16 μm thick inner layer of β-phase brass and a 14 μm thick surface layer of γ-phase brass, -Pull to 0.25mm.
19. A method for producing an electrode wire according to any one of claims 1 to 15, The following steps are involved: - Take a brass core with a diameter of 1.20 mm containing 60% copper and 40% zinc, - depositing a 13 μm thick zinc layer on the core, - The wire is pulled to 0.464 mm and then the zinc layer is 5 μm thick, - the blank thus obtained is subjected to a diffusion heat treatment consisting in raising the temperature from room temperature to a stationary stage of 140° C. for 11 hours over 4 hours, and then lowering the temperature to room temperature over 5 hours; the coating then comprises an inner layer of gamma brass of about 6 μm and a surface layer of epsilon brass of about 2 μm thick, without traces of unalloyed zinc; - Gradually drawn to a final diameter, advantageously 0.20 mm, 0.25 mm or 0.30 mm.
